Verbals Bullying Related to Self-Esteem on Adolescents - Jek Amidos Pardede; Akhyarul Huda; Masri Saragih; Marthalena Simamora (JENDELA NURSING JOURNAL, 2021)
Background: Bullying is a problem of global concern that can have serious / negative effects on the mental health and well-being of adolescents. Bullying that often occurs is verbal bullying which can affect self-esteem. Purpose: to determine the relationship between bullying and self-esteem on adolescents. Methods: the design of this research is descriptive correlation with cross sectional approach. The population of the study were 83 students of class X Senior High School who experienced bullying and the sample of this study was the entire population with the sampling technique using total sampling. The data collection tool used a questionnaire that had been tested for validity and reliability, the statistical test used was the chi-square test with p 0.05. Results: the study showed that the majority of verbal bullying was moderate as much as 43.4% and the majority of the majority were low self-esteem as much as 46.6% with p = 0.004.Conclusion: there is a significant relationship between verbal bullying and self-esteem.